2012
DOI: 10.1097/inf.0b013e31823a0d6e
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviral Meningitis and Concurrent Peripheral Motor Axonal Polyneuropathy

Abstract: Enteroviral infections can cause acute flaccid paralysis resulting from anterior myelitis, but the occurrence of axonal polyneuropathy is not well described. We report an 8-year-old boy who presented with symmetric, ascending flaccid paralysis and was diagnosed with concurrent echovirus type 9 viral meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…(2) excessive costs are associated with such evaluations; (3) provider belief that the vaccine was the likely cause; or (4) the provider was not aware of how to conduct such an evaluation. CISA reviewed serious neurologic adverse events reported to VAERS after the pandemic H1N1 influenza vaccine 7 and found that when etiologic investigations were conducted, alternate (more likely) causes of the AEFI were often identified (eg, the occurrence of Campylobacter, Mycoplasma, or cytomegalovirus infections before Guillain-Barr e syndrome).…”
Section: General Approach To Evaluating Serious Aefimentioning
confidence: 99%
See 1 more Smart Citation
“…(2) excessive costs are associated with such evaluations; (3) provider belief that the vaccine was the likely cause; or (4) the provider was not aware of how to conduct such an evaluation. CISA reviewed serious neurologic adverse events reported to VAERS after the pandemic H1N1 influenza vaccine 7 and found that when etiologic investigations were conducted, alternate (more likely) causes of the AEFI were often identified (eg, the occurrence of Campylobacter, Mycoplasma, or cytomegalovirus infections before Guillain-Barr e syndrome).…”
Section: General Approach To Evaluating Serious Aefimentioning
confidence: 99%
“…Because of the temporal relationship, one may suspect the immunizations as the cause, yet subsequent isolation of enterovirus from cerebrospinal fluid implicates the enteroviral infection instead. 3 The term adverse event following immunization (AEFI) is defined as any untoward event that occurs after immunization, regardless of causal association. 4 AEFI is the preferred notation to describe such clinical events because the term is free from implications regarding causal relationship and favors an open mind about the role of immunizations.…”
mentioning
confidence: 99%